Agenesis of Corpus Callosum and Emotional Information Processing in Schizophrenia - Stip, Emmanuel; Lungu, Ovidiu (Frontiers in Psychiatry, 2012)
Corpus callosum (CC) is essential in providing the integration of information related to perception and action within a subcortico-cortical network, thus supporting the generation of a unified experience about and reaction to changes in the environment. Its role in schizophrenia is yet to be fully elucidated, but there is accumulating evidence that there could be differences between patients and healthy controls regarding the morphology and function of CC, especially when individuals face emotionally laden information. Here, we report a case study of a patient with partial agenesis of corpus callosum (agCC patient with agenesis of the anterior aspect, above the genu) and we provide a direct comparison with a group of patients with no apparent callosal damage (CC group) regarding the brain activity during the processing of emotionally-laden information. We found that although the visual cortex activation in response to visual stimuli regardless of their emotional content was comparable in agCC patient and CC group both in terms of localization and intensity of activation, we observed a very large, non-specific and non-lateralized cerebral activation in the agCC patient, in contrast with the CC group, which showed a more lateralized and spatially localized activation, when the emotional content of the stimuli was considered. Further analysis of brain activity in the regions obtained in the CC group revealed that the agCC patient actually had an opposite activation pattern relative to most participants with no CC agenesis, indicating a dysfunctional response to these kind of stimuli, consistent with the clinical presentation of this particular patient. Our results seem to give support to the disconnection hypothesis which posits that the core symptoms of schizophrenia are related to aberrant connectivity between distinct brain areas, especially when faced with emotional stimuli, a fact consistent with the clinical tableau of this particular patient.